International variation in place of death of older people who died from dementia in 14 European and non-European countries - Reyniers, Thijs; Deliens, Luc; Pasman, H Roeline; Morin, Lucas; Addington-Hall, Julia; Frova, Luisa; Cardenas-Turanzas, Marylou; Onwuteaka-Philipsen, Bregje; Naylor, Wayne; Ruiz-Ramos, Miguel; Wilson, Donna M; Loucka, Martin; et al. (Journal of the American Medical Directors Association, 2015)
OBJECTIVES: The objective of this study was to examine variation in place of death of older people dying from dementia in countries across 4 continents. DESIGN: Study of death certificate data. METHODS: We included deaths of older (65 + years) people whose underlying cause of death was a dementia-related disease (ICD-10: F01, F02, F03, G30) in Belgium, the Netherlands, England, Wales, France, Italy, Spain, Czech Republic, Hungary, New Zealand, United States, Canada, Mexico and South Korea. We examined associations between place of death and sociodemographic factors, social support, and residential and health care system factors. RESULTS: Overall, 4.8% of all deaths were from a dementia-related disease, ranging from 0.4% in Mexico to 6.9% in Canada. Of those deaths, the proportion occurring in hospital varied from 1.6% in the Netherlands to 73.6% in South Korea. When controlling for potential confounders, hospital death was more likely for men, those younger than 80, and those married or living in a region with a higher availability of long-term care beds, although this could not be concluded for each country. Hospital death was least likely in the Netherlands compared with other countries. CONCLUSIONS: Place of death of older people who died from a dementia-related disease differs substantially between countries, which might point to organizational differences in end-of-life care provision. Increasing the availability of long-term care beds might be important to reduce the number of hospital deaths, while focusing specialized end-of-life care services on married people or those aged 65 to 79 might be crucial for achieving home death. However, proper end-of-life care needs to be ensured in hospitals, should this be the most appropriate end-of-life care setting.
Keywords: Internationality; Nový Zéland; dlouhodobá péče; Databases, Factual; logistické modely; Severity of Illness Index; Death Certificates; Odds Ratio; interval spolehlivosti; pečovatelské domovy; stupeň závažnosti nemoci; Evropa; Europe; multivariační analýza; Korea; úmrtní listy; mortalita v nemocnicích; zeměpis; odds ratio; Logistic Models; ženské pohlaví; New Zealand; lidé; Cause of Death; Dementia; internacionalita; mužské pohlaví; senioři; Geography; příčina smrti; Aged, 80 and over; demence; Aged; senioři nad 80 let; Confidence Intervals; databáze faktografické; Humans; péče o umírající; Nursing Homes; Hospital Mortality; Female; Terminal Care; Long-Term Care; Male; Multivariate Analysis